Investigation of thiol-disulphide balance in patients with acute urticaria and chronic spontaneous urticaria. (3rd July 2017) - Akbas, Ayse; Kilinc, Fadime; Sener, Sertac; Aktaş, Akın; Baran, Pervin; Ergin, Merve
Abstract: Background : Thiol–disulphide balance plays a major role in health and diseases. This balance may be disrupted by various diseases. We aimed to determine status of the effect of thiol–disulphide balance in urticaria. Objectives : We aimed to investigate the thiol–disulphide balance in patients with acute urticaria (AUP) and chronic spontaneous urticaria (CSU). Methods : Study included 53 AUP and 47 healthy controls plus 57 patients with chronic spontaneous urticaria (CSUP) and 57 healthy controls. Levels of native thiols, disulphides and total thiols were evaluated in plasma using a new and automated spectrophotometric method. Ratios of disulphides/total thiols, disulphides/native thiols and native thiols/total thiols were calculated. Results : For AU, there was no statistical difference compared to control group in levels of native thiols, disulphides and total thiols. For CSU, however, there was an increase in levels of native thiols, disulphides and total thiols and the ratio of thiol/disulphide in favour of disulphide. Conclusion : Thiol–disulphide balance was not affected by AU but shifted towards to disulphide in CSU indicating the presence of oxidative stress (OS).